THE EFFECT OF MINIMAL MARKING FEEDBACK FOR TEACHING PARAGRAPH WRITING - Surya Darmawan; Irma Savitri Sadikin; Yanuarti Apsari (IKIP Siliwangi, 2020)
Giving feedback to the students can help them to be better in their writing skill. Therefore, the teacher should give an alternative way in giving feedback to encourage students to master writing skill. There are a lot of kinds of feedback, one of them is using minimal marking feedback. The main objective of this study is to investigate the effectiveness of minimal marking feedback towards students’ ability in writing descriptive text. It used quantitative method with quasi-experimental design to get the result. It was conducted in one of Junior High Schools in West Java with two classes as the samples. The process started by dividing the students into two categories, namely experimental group and control group. The group which was given treatment by minimal marking feedback in writing descriptive text was experimental one. The treatment was given in five meetings for experimental group. Meanwhile, the control group did not have that treatment for writing the descriptive text. After having the treatment for five meetings, it can be seen that there was significant improvement for those who are in experimental group. This was proven by the data calculated by IBM SPSS Statistics version 23. The result of the calculation by using T-Test showed that Sig.(2-tailed) is 0.000 which was lower than 0.05 meaning that the null hypothesis was rejected. Therefore, the treatment which was given to experiment group was significantly improve students’ ability in writing descriptive text. Keywords: Writing, Descriptive text, Minimal Marking Feedback